2010
DOI: 10.5012/bkcs.2010.31.7.2019
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between IGFBP-5 and TNFR1

Abstract: Insulin-like growth factor binding protein 5 (IGFBP-5) plays an important role in controlling cell survival, differentiation and apoptosis. Apoptosis can be induced by an extrinsic pathway involving the ligand-mediated activation of death receptors such as tumor necrosis factor receptor 1 (TNFR1). To determine whether IGFBP-5 and TNFR1 interact as members of the same apoptosis pathway, recombinant IGFBP-5 and TNFR1 were isolated. The expression and purification of the full-length TNFR1 and truncated IGFBP-5 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In addition to VEGFA and TGF- β , TNF-α is another important cytokine correlated with IGFBP5, although TNF-α expression and survival prognosis were not significant different between KIRP patients and controls. There has been reported that IGFBP-5 inhibits TNF-α by competitively binding to TNFR1 [24, 25]. We hypothesize that downregulated IGFBP5 expression might release the binding domain of TNFR1 to restore apoptosis induced by TNF-α in cancer cells.…”
Section: Discussionmentioning
confidence: 84%
“…In addition to VEGFA and TGF- β , TNF-α is another important cytokine correlated with IGFBP5, although TNF-α expression and survival prognosis were not significant different between KIRP patients and controls. There has been reported that IGFBP-5 inhibits TNF-α by competitively binding to TNFR1 [24, 25]. We hypothesize that downregulated IGFBP5 expression might release the binding domain of TNFR1 to restore apoptosis induced by TNF-α in cancer cells.…”
Section: Discussionmentioning
confidence: 84%